The Prognostic Synergy of Classic Cytokines (IL-6, IL-1β, TNF-α, TGF-β) and Emerging Biomarkers (Galectin-3, FGF-23) in Predicting Renal and Cardiovascular Outcomes in Patients with Stage 3-4 Chronic Kidney Disease: Cytokine & Partner Biomarkers in CKD Prognosis - Zhai , Wenliang; Guo , Shubin (Journal of Medical Biochemistry, 2026)
Background: Chronic Kidney Disease (CKD) progression is driven by intertwined pathways of inflammation, fibrosis, and disordered mineral metabolism. While cytokines like IL-6 and TNF-α are established inflammatory markers, their prognostic value may be enhanced by combining them with emerging partners like Galectin-3 (Gal-3, fibrosis/pro-inflammatory amplifier) and Fibroblast Growth Factor-23 (FGF-23, mineral bone disorder). We investigated the individual and combined prognostic power of this novel panel for renal and cardiovascular (CV) outcomes.Methods: In this prospective, single-center cohort study, 218 patients with CKD stages 3-4 were enrolled. Baseline serum levels of IL-6, IL-1β, TNF-α, TGF-β, Gal-3, and FGF-23 were measured. Patients were followed for 36 months for a primary composite endpoint: ≥40% decline in eGFR, progression to kidney failure requiring replacement therapy (KFRT), or a major adverse CV event (MACE). Cox proportional-hazards models, Kaplan-Meier analysis, and receiver operating characteristic (ROC) curves were employed.Results: Over 36 months, 68 patients (31.2%) reached the composite endpoint. Elevated levels of all biomarkers, except IL-1β, were individually associated with the endpoint in univariate analysis. In multivariate Cox regression, only IL-6 (HR: 1.82, 95% CI: 1.30-2.55), Gal-3 (HR: 2.15, 95% CI: 1.45-3.18), and FGF-23 (HR: 1.95, 95% CI: 1.35-2.82) remained independent predictors after adjustment for age, diabetes, eGFR, and albuminuria. A "Triple-Biomarker Risk Score" (TBRS), combining tertiles of IL-6, Gal-3, and FGF-23, showed a powerful graded association with risk. Patients in the high-TBRS group had a 9-fold higher risk (HR: 9.10, 95% CI: 3.82-21.68) compared to the low-score group. The area under the ROC curve (AUC) for the TBRS (0.84) was significantly superior to that of eGFR alone (0.72, p
Keywords: Chronic Kidney Disease, Inflammation, Fibrosis, FGF-23, Galectin-3, Prognosis, Biomarkers.